ÜÇ BOYUTLU HÜCRE OLUŞTURMA PROBLEMİNE ÇOK AMAÇLI BİR ÇÖZÜM YAKLAŞIMI - Feriştah ÖZÇELİK; Tuğba SARAÇ (Eskişehir Osmangazi Üniversitesi Mühendislik ve Mimarlık Fakültesi Dergisi, 2021)
Three-dimensional cell formation problem deals with grouping the parts, machines and workers together and assigning these groups to the cells. The main objectives of this problem are to minimize the number of exceptional elements and voids. It is seen that in most of the studies in the literature on this subject, these two objectives are summed and the problem is taken in a single objective manner. In this study three dimensional cell formation problem is considered as a multi-objective problem. Augmented constraint method is used to scalarize the objectives. Obtained solutions are compared with the results from the literature and 30 new non-dominant solutions are found for the used test set